Contribuições para o estudo do DFIG diante de afundamentos desbalanceados: detecção e LVRT - Dantas, Joacillo Luz (2017)
The global warming and the pollution on earth have driven the world demand for non-polluting electric power sources, and the wind turbines are one of the main sources of energy used for this purpose. The wind turbines are widespread on the world, and the number of wind farms connected to the grid is constantly increasing. In this scenario, the double fed induction gene- rator (DFIG) plays an important role, since it is one of the most used wind generator. The main advantage of this machine is to provide variable speed using a small and economic back-to-back power converter. Actually , the converter only need to be sized to 30% of the rated power of the DFIG. However, the DFIGs are very sensitive to grid disturbances, especially to voltage sags. Voltage sag is one of the major factors that contribuite to the power quality deterioration, and it has a negative influence in the DFIG because this machine has the stator circuit directly connected to the grid. The voltage sag can provoque oscillations in the active power, in the torque and in the DC link voltage, and it can also damage the machine and the back-to-back converter due to the high currents that arise in this type of contingency. Thus, it is mandatory to apply a control strategy to help the DFIG to stay connected to the grid during voltage sags and to overcomes this stressful mishap, as well as the necessity of voltage sag detection in order to make the control strategy acts at the right time. Therefore, by introducing the concept of aggre- gated value of the normalized voltage per phase, this work proposes a rapid and robust voltage sag detection algorithm, named ADAMF. It is able to quickly and accurately detect symmetric and asymmetric voltage sags, even within distorted voltage systems. This work also proposes a control strategy applied to the rotor side converter (RSC) of the DFIG, in order to protect the machine and the back-to-back converter during voltage sags. The aim of the proposed strategy control is to remove the oscillating active power that raises during unbalanced voltage sags, and as consequence, the reduction of the machine currents.